PENGARUH TEKNOLOGI DAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Cici Lucya; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze how the influence of technology and education on economic growth in Indonesia from 2011-2017. This study uses secondary data sourced from the Indonesian Central Bureau of Statistics with research variables grouped into two parts, namely the dependent variable in this study defined as economic growth and independent variables consisting of the education level of the population of Indonesia and Indonesian Technology. This study uses multiple linear regression methods to find the relationship between the independent variables and the dependent variable, from the results of statistical estimates showing that the level of education has a positive influence on Indonesia's economic growth and technology is also found to have a positive influence on the level of economic growth in Indonesia.